Features of the clinical presentation and course of community-acquired pneumonia against the background of type 2 diabetes mellitus - A. A. Zaytseva; E. B. Bukreeva; T. S. Ageeva; M. A. Zorkaltsev; T. V. Saprina; V. D. Udodov; M. M. Ardashirov (Бюллетень сибирской медицины)
Community-acquired pneumonia remains the leading infectious cause of death around the world. Many factors influence the prognosis and outcome of this disease. Compared with healthy individuals, patients with diabetes mellitus are at increased risk of respiratory tract infections, such as community-acquired pneumonia. Diabetes mellitus contributes to the development of pulmonary thrombotic microangiopathy, changing the functional state of the lungs. In numerous studies involving patients with diabetes mellitus, data on the state of the lungs were obtained by instrumental tests, such as spirometry, ventilation / perfusion scintigraphy, perfusion computed tomography, and diffusing capacity of the lungs for carbon monoxide. In patients with community-acquired pneumonia, diabetes mellitus causes vague clinical symptoms, leads to a severe course of the disease, and contributes to development of complications. Diagnosing the functional state of the lungs in patients with community-acquired pneumonia against the background of diabetes mellitus has not been studied.